2017
DOI: 10.1038/bmt.2017.98
|View full text |Cite
|
Sign up to set email alerts
|

Elevated bone marrow eosinophil count is associated with high incidence of severe acute GvHD after allogeneic hematopoietic stem cell transplantation

Abstract: Predicting severe acute GvHD (aGvHD) after allogeneic hematopoietic stem cell transplantation (HSCT) is challenging but critical. Mild aGvHD may have a favorable impact on relapse, whereas severe aGvHD is associated with poor outcomes. The aim of this study was to evaluate whether elevated eosinophil count in the bone marrow (BM) at 1 month after HSCT is associated with a high incidence of new and severe aGvHD. We enrolled 101 consecutive patients; median age was 50 years, and 50.5% patients were male. The med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…McNeel et al 13 reported that HE from PB often is the presenting sign of acute graft versus host disease (aGVHD) and increased IL‐5 and IL‐5 mRNA expression in blood and skin biopsies were suggestive of a correlation between eosinophilia and aGVHD. There are also reports that eosinophilia from BM not PB, is associated with the development of aGVHD 14,15 . Based on these findings assessment of eosinophilia by BM examination after BMT serves a predictive role for the clinical course after BMT.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…McNeel et al 13 reported that HE from PB often is the presenting sign of acute graft versus host disease (aGVHD) and increased IL‐5 and IL‐5 mRNA expression in blood and skin biopsies were suggestive of a correlation between eosinophilia and aGVHD. There are also reports that eosinophilia from BM not PB, is associated with the development of aGVHD 14,15 . Based on these findings assessment of eosinophilia by BM examination after BMT serves a predictive role for the clinical course after BMT.…”
Section: Introductionmentioning
confidence: 90%
“…There are also reports that eosinophilia from BM not PB, is associated with the development of aGVHD. 14,15 Based on these findings assessment of eosinophilia by BM examination after BMT serves a predictive role for the clinical course after BMT. On the contrary, Sato et al 16 suggested that presentation of eosinophilia can be a favorable prognostic marker after BMT.…”
mentioning
confidence: 99%
“…To provide simple risk stratification, we divided our patients into two risk groups (CD38 HIGH and CD38 LOW ) by employing the survival classification and regression tree (CART) analysis. CART analysis is an empirical statistical technique based on recursive partitioning analysis and it is useful to arrive at clinical decisions and risk stratification models 10,11 . The two patient risk groups were treated as an ordered categorical variables, and the impacts on endpoints were evaluated using the above‐mentioned methods.…”
Section: Methodsmentioning
confidence: 99%
“…CART analysis is an empirical statistical technique based on recursive partitioning analysis and it is useful to arrive at clinical decisions and risk stratification models. 10,11 The two patient risk groups were treated as an ordered categorical variables, and the impacts on endpoints were evaluated using the above-mentioned methods. For comparison between groups, patients and disease characteristics were compared using the Mann-Whitney U test for continuous variables and chi-square test for categorical variables.…”
Section: Endpoints and Statistical Analysismentioning
confidence: 99%